Toward an Ontology of Peace I: Ricoeur on Peace and Violence in the Ontology of Creation - Gregor, Brian (Approaching religion, 2024)
This essay is the first of two seeking to draw out an ontology of peace from Paul Ricoeur’s thought. This first essay (Part I) argues that Ricoeur’s hermeneutics of creation provides the best starting point because of its insistence on the goodness of created being. Ricoeur develops this conviction from his reading of the biblical creation accounts, which I follow through three texts from three periods of Ricoeur’s work. In The Symbolism of Evil, Ricoeur show that peace rather than violence is most fundamental to creation. In his essay "On the Exegesis of Gen 1:1-2:4a," he expands his interpretation to consider the combat imagery in the Psalms, but shows how the text interprets the separation and ordering of creation as a work of providential wisdom rather than violence. In Thinking Biblically, Ricoeur complicates his earlier hermeneutics of creation by bringing in themes of mastery, chaos, and fragility—three themes that need careful interpretation in order to preserve Ricoeur’s earlier emphasis on the goodness and peacefulness of creation. This preservation is possible, I argue, by recovering Ricoeur’s early Christological reflections in The Symbolism of Evil, which point to the hope of an ultimate, eschatological victory over violence. I conclude by arguing that Ricoeur’s hermeneutics can help us to imagine peace, which is crucial to the practice of peace.